2007
DOI: 10.1108/17506180710729628
|View full text |Cite
|
Sign up to set email alerts
|

Tourist shoppers' satisfaction with regional shopping mall experiences

Abstract: Purpose -The purpose of this paper is to assess whether tourist shopper segments are an attractive market for shopping centers. This research aims to explore whether or not tourist shoppers are more satisfied than resident shoppers with their shopping experience and whether tourist shoppers have the intention to spend more than their resident shopper counterparts. Design/methodology/approach -Data for this report come from personal face-to-face mall intercepts of shoppers (n ¼ 578) in two new generation malls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 25 publications
2
71
0
1
Order By: Relevance
“…LeHew and Wesley (2007) examined the level of satisfaction among area residents and tourists for two shopping malls in the Midwest and two heritage destination centers on the West Coast (San Francisco and Las Vegas). The researchers concluded that the area residents demonstrated higher levels of satisfaction with the shopping venues.…”
Section: Shopping As a Tourist Activitymentioning
confidence: 99%
“…LeHew and Wesley (2007) examined the level of satisfaction among area residents and tourists for two shopping malls in the Midwest and two heritage destination centers on the West Coast (San Francisco and Las Vegas). The researchers concluded that the area residents demonstrated higher levels of satisfaction with the shopping venues.…”
Section: Shopping As a Tourist Activitymentioning
confidence: 99%
“…In the tourism paradigm, two constructs (internal and external) encourage tourists to buy (i.e., Babin, Darden, & Griffin, 1994;DeSarbo & Edwards, 1996;Kahle, Beatty, & Homer, 1986;Sheth, Newman, & Gross, 1991). Push motivators are connected to internal or emotional aspects (Donovan, Rossiter, Marcoolyn, & Nesdale, 1994;LeHew & Wesley, 2007), which may inspire tourists to make planned purchases. In contrast, pull motivators are related to external, situational or cognitive aspects, which many create a sense of impulsive or irresistible buying behavior (Rook & Fisher, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, shopping activity is considered an integral part of tourism (LeHew & Wesley, 2007). According to Liu et al, (2008), the retail sector contributes a significant proportion to the tourism industry and plays an important role in maintaining a destination's attractiveness.…”
Section: H1: Affordable Luxury's Epps Creates a Positive Impact On Trmentioning
confidence: 99%